The Influence of Hybrid Work Patterns on Organizational Engagement and Work Stress - Olaus, Hugo; Veronica, Annelie; Alfred, Alfred (PELNUS | Pen en Light for Natural Union of Science, 2025)
This study investigates the influence of hybrid work patterns on organizational engagement and work stress among employees in organizations that have adopted flexible work systems after the COVID-19 pandemic. The emergence of hybrid work combining remote and in-office arrangements has transformed organizational culture, communication, and performance management, raising critical questions about its impact on employee well-being and commitment. Using a quantitative research design, data were collected through Likert-scale questionnaires measuring hybrid work flexibility, engagement (using the Utrecht Work Engagement Scale), and stress (using the Perceived Stress Scale). The data were analyzed using regression and Structural Equation Modeling (SEM) to examine the relationships between variables. The results indicate that hybrid work flexibility significantly enhances organizational engagement by increasing employees’ sense of autonomy and control over their work. However, excessive remote working and poorly structured flexibility contribute to higher levels of work stress due to blurred boundaries and social isolation. Moderating variables such as work-life balance, social support, and leadership style were also identified as influential in shaping these outcomes. The study concludes that hybrid work has both empowering and challenging aspects boosting engagement when autonomy is balanced with clear communication and organizational support, yet increasing stress when boundaries and connections are neglected. The findings suggest that organizations should implement hybrid policies that promote engagement, psychological well-being, and structured flexibility to achieve sustainable performance. This research contributes to the literature by integrating the Job Demands-Resources (JD-R) Model, Self-Determination Theory, and Social Exchange Theory to explain how hybrid work environments influence employee motivation and stress regulation in the modern workplace.